Pengelompokan Fungsi Aktif Senyawa Data SMILES (Simplified Molecular Input Line Entry System) Menggunakan Metode K-Means Dengan Inisialisasi Pusat Klaster Menggunakan Metode Heuristic O(N LogN) - Sherly Witanto; Dian Eka Ratnawati; Syaiful Anam (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Active compounds have function as a medicine that can prevent or cure diseases. Some of the active compounds have been known the function and some are still in the research stage. Currently in Indonesia there is still no program that capable to classifying chemical compounds as drugs for certain diseases. SMILES notation is the conversion of chemical compounds in the form of line notation. Notation SMILES able to provide convenience to the process of computerization on the classification of chemical compounds. The classification of the SMILES notation is carried out by taking the values ​​of the B, S, N, O, I, F, C, P, Cl, Br and OH atoms present in the compound. Before being processed, to get the value of the feature is done by dividing the process of each atom with the length of the compound. K-Means algorithm is the most widely used clustering method because it is easy and simple. The grouping of active function using K-Means method has weakness in random cluster initialization process, so that heuristic method o (n logn) is used to get the cluster initials with better value. Based on the software that has been made, the test is done using 512 of training data and test data as much as 128. Accuracy obtained from the test that is equal to 63% and testing using ¬K-Fold Cross Validation with 10 times the test produces an average accuracy of 52,58 %. Testing using K-Means with heuristic o (n logn) yielded better accuracy compared to conventional K-Means.